Endophilin-A1 BAR domain interaction with arachidonyl CoA - Petoukhov, Maxim V.; Weissenhorn, Winfried; Svergun, Dmitri I. (Frontiers in Molecular Biosciences, 2014)
Endophilin-A1 belongs to the family of BAR domain containing proteins that catalyze membrane remodeling processes via sensing, inducing and stabilizing membrane curvature. We show that the BAR domain of endophilin-A1 binds arachidonic acid and molds its coenzyme A (CoA) activated form, arachidonyl-CoA into a defined structure. We studied low resolution structures of endophilin-A1-BAR and its complex with arachidonyl-CoA in solution using synchrotron small-angle X-ray scattering (SAXS). The free endophilin-A1-BAR domain is shown to be dimeric at lower concentrations but builds tetramers and higher order complexes with increasing concentrations. Extensive titration SAXS studies revealed that the BAR domain produces a homogenous complex with the lipid micelles. The structural model of the complexes revealed two arachidonyl-CoA micelles bound to the distal arms of an endophilin-A1-BAR dimer. Intriguingly, the radius of the bound micelles significantly decreases compared to that of the free micelles, and this structural result may provide hints on the potential biological relevance of the endophilin-A1-BAR interaction with arachidonyl CoA.